Risk factors for obstructive sleep apnea in cystic fibrosis. Issue 4 (11th January 2022) - Shakkottai, Aarti; Irani, Sanaya; Nasr, Samya Z.; O'Brien, Louise M.; Chervin, Ronald D.
Abstract: Introduction: Despite emerging data that suggest a high frequency and severity of obstructive sleep apnea (OSA) among patients with cystic fibrosis (CF), few of them are referred for polysomnography. Little is known about which patients with CF are at increased risk for OSA and which sleep symptoms merit investigation. Methods: A single‐center retrospective analysis of clinical and polysomnographic data from 2009, January 1 to October 31, 2020 in referred children and adults with CF. Results: Among 74 patients (42 children, 32 adults) with CF, 39 (53%) had OSA. No age or sex differences emerged in OSA frequency. Mean apnea–hypopnea index (AHI) was higher among overweight/obese adults ( n  = 16) as compared with adults of normal weight or underweight (11.4 vs. 6.2; p  = 0.005). Adults with ( n  = 10) versus without a crowded oropharynx had 13.0 times greater odds of OSA (95% confidence interval (CI): 1.4, 121.4; p  = 0.02). Children with ( n  = 24) versus without tonsillar hypertrophy had a higher risk for OSA (OR = 5.2; 95% CI: 1.4, 19.8; p  = 0.02), as did children with ( n  = 10) versus without symptomatic chronic sinusitis (OR = 5.8; 95% CI: 1.1, 32.1; p  = 0.04). Neither snoring, excessive daytime sleepiness, nor lung disease severity were associated with OSA. Conclusion: Key risk factors for OSA may differ between children and adults with CF: upper airway pathology appears important in children and overweight/obesity or a crowded oropharynx in adults. Given the lack of sensitivity of snoring, daytime sleepiness, and lung disease severity, detection of OSA may require a low threshold for polysomnographic assessment in this vulnerable population.